Transformasi Nāsikh-Mansūkh dalam Pandangan as-Suyūṭī: Respons terhadap Dinamika Sosial dan Kebutuhan Masyarakat - Aswindasari, Aliffia (Sunan Kalijaga Islamic State University, 2024)
As-Suyūṭī’s reconstruction of the nāsikh-mansūkh concept responds to shifts in social and historical contexts, aiming to maintain its relevance and applicability for Muslims. This study seeks to explore his stance on nāsikh-mansūkh by linking it to the legal reform mechanisms he developed. Utilizing a qualitative method within a sociology of knowledge framework, the research found that as-Suyūṭī’s understanding of nāsikh-mansūkh emerged from synthesizing previous thoughts, adapted to meet the needs of his era. As-Suyūṭī saw nāsikh-mansūkh as a concept born out of the evolving needs for new laws due to contextual changes. This perspective underpinned his argument for issuing various fatwas. This approach took shape in a society facing degradation in various aspects, necessitating new laws to address emerging needs. His pragmatic way of thinking was driven by the specific needs of his time, leading him to reconceptualize issues previously unrelated. This inclination led as-Suyūṭī to reject certain verses classified as nāsikh-mansūkh by earlier scholars, arguing that they no longer met societal needs. His adaptive approach diverged from the traditional thinking of his contemporaries in Islamic jurisprudence, sparking significant polemics and debates.